Ecological Restoration in Protected Area of Peat Swamp Forest as an Effort to Build Socio-Ecological Resilience in Sebangau National Park Central Kalimantan, Indonesia - Anna Amalia (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
Peat forests are unique and sensitive ecosystems, have complex hydrological systems and bear important economic service functions. In Southeast Asian countries, peatland degradation has been increasingly severe in the last decade due to the exploitation of natural resources, which concerns the structure and function of the system. Ecological rehabilitation, including hydrological restoration, is believed to be useful for restoring the function of forest/peat swamp systems. Protection of critical areas in the form of National Park is also applied to reduce disturbance and further degradation of the area. A literature review is conducted to analyze the extent to which ecological restoration can achieve system resilience, especially socio-ecological resilience as a 'complex-adaptive system' using resilience concepts. The linkage between the ecological function of peat forest restoration by restoring hydrological systems, the diversity of flora and fauna, and enhancing social resilience with social networking and community livelihood is an important key in achieving resilience. Area Protection (in the form of National Park) needs to pay attention to interconnection systems in the